Preučevanje otroške in mladinske književnosti - Zorman, Barbara; Tucovič Sturman, Vladka; Zavrl, Andrej; Giacometti, Kristina; Požin, Karin; Haramija, Dragica; Batič, Janja; Baloh, Barbara; Petrović, Vanja; Kos-Lajtman, Andrijana; Radić, Damir; Krevel, Alja; et al. (University of Maribor Press, 2025)
Studying children’s and YA literature. The monograph presents three different issues which are relatively complete in their own right and at the same time also interdependent: (1) terminological questions linked to children’s and YA literature: thematology, literary types and forms of reading materials, literary canonisation, intertextuality; (2) evaluating children’s and YA literature, the basic criteria; (3) theories of reading development and reading: addressee age or the development of reading literacy skills of young readers; the criteria of text length and number of different words in the text (connected with components of reading literacy). There have been significant changes over recent years in how literary works for children and young adults are created, designed, published and evaluated. The reading development of children, pupils and students is studied by various disciplines, and it is therefore appropriate for all these experts to collaborate, taking into account the principles of literary history, literary theory, and literary reception.